Resilience and Resistance: Indigenous Agency of Hawai’ian Indigene in Lynn Kalama Nakkim’s Mahele o Maui - Indriyanto, Kristiawan (OKARA: Jurnal Bahasa dan Sastra, 2022)
In recent years, the emergence of indigenous literature contextualizes the historicity of colonialism and the ensuing resistance. This present study articulates how the Native Hawaiâ€™ians articulate their resistance against American domination through the resilience of their cultural heritage and advocates for political changes, as is reflected in Lynn Kalama Nakkimâ€™s Mahele o Maui. The study applied an econarratological perspective which foregrounds the reader’s active role in reimagining a different socio-cultural perspective of the natural environment from Maheleâ€™s perspective and engaging with other (non-Western) environmental imagination. The theory of resilience and resistance, as stated by Adamson and Molina, underlines how indigenous Hawaiâ€™ian tradition manages to persevere and transform through the Western model of narration, a novel. The study explores how Nakkimâ€™s fiction articulates the indigenous epistemology of Aloha Aina to actively resist American domination with the eventual goal of achieving sovereignty and independence. The finding concludes how Native Hawaiâ€™iansâ€™ literature has a similar concern with other indigenous struggles in the world, advocative and politically oriented in outlook, echoing their struggle for the right of self-determination and eventual sovereignty.